A DOUBLE-EDGED SWORD OF CHATGPT IN STUDENTS’ WRITING PROCESS HIGHLIGHTING BENEFITS AND POTENTIAL DANGERS - Khairunisa, Hani; Novita Sari, Ratih (ELLTER Journal, 2026)
The integration of Artificial Intelligence (AI) like ChatGPT into education presents a double-edged sword for the student writing process. This research explores the benefits and potential dangers of using ChatGPT for writing exposition texts among senior high school students. Using a qualitative approach with an interpretative phenomenological analysis (IPA) design, this research collected data from ten XI.2 Inglan 2 students through in-depth interviews, observation, and document analysis. The findings reveal that ChatGPT is highly beneficial across all writing stages: assisting with idea generation and outlining in pre-writing, structuring paragraphs in drafting, and improving grammar and coherence during revision. However, two significant dangers were identified: a growing dependency that risks weakening students' critical thinking, and a loss of originality, as students felt their writing became "generic" and lacked a personal voice. This research concludes that while ChatGPT is a powerful tool, its use must be balanced. Educators should guide students toward responsible AI use, fostering critical AI literacy to ensure technology supports, rather than replaces, the development of authentic writing skills.